epithelial cytological atypia associated with intrauterine contraceptive devices - Hassan, maha Shakir (Journal of the Faculty of Medicine Baghdad, 2007)
Background: prolonged usage of an intrauterine contraceptive device (IUD) is often associated with exfoliation of a typical cells.